The impact of heterogeneity of the air-blood barrier on control of lung extravascular water and alveolar gas exchange - Miserocchi, Giuseppe (Frontiers in Network Physiology, 2023)
The architecture of the air-blood barrier is effective in optimizing the gas exchange as long as it retains its specific feature of extreme thinness reflecting, in turn, a strict control on the extravascular water to be kept at minimum. Edemagenic conditions may perturb this equilibrium by increasing microvascular filtration; this characteristically occurs when cardiac output increases to balance the oxygen uptake with the oxygen requirement such as in exercise and hypoxia (either due to low ambient pressure or reflecting a pathological condition). In general, the lung is well equipped to counteract an increase in microvascular filtration rate. The loss of control on fluid balance is the consequence of disruption of the integrity of the macromolecular structure of lung tissue. This review, merging data from experimental approaches and evidence in humans, will explore how the heterogeneity in morphology, mechanical features and perfusion of the terminal respiratory units might impact on lung fluid balance and its control. Evidence is also provided that heterogeneities may be inborn and they could actually get worse as a consequence of a developing pathological process. Further, data are presented how in humans inter-individual heterogeneities in morphology of the terminal respiratory hinder the control of fluid balance and, in turn, hamper the efficiency of the oxygen diffusion-transport function.